Macro and microscopic evaluation of the digestive tract of broilers fed a diet containing glycerin - Sousa, Denise Cerqueira; Oliveira, Nadja Lamonye Alves; Santos, Edna Teles dos; Dourado, Leilane Rocha Barros; Ferreira, Guilherme José Bolzani de Campos (Comunicata Scientiae, 2017)
This study aimed to evaluate the presence of morphological changes in the digestive tract of broilers fed diets containing 7% glycerol. It was used 16 animals from male Cobb 500® line, distributed in a completely randomized design in two treatments: animals fed diet without glycerin and animals fed diets containing 7% glycerol. It was observed that the addition of glycerin at 7% in the diet of broilers promotes the occurrence of significant inflammatory infiltrates in the proventriculus, caecum and colon of such animals, macroscopically the addition of glycerin in the diet did not cause any significant difference, but these differences had no significant effect on zootechnical development of such animals. It is possible to conclude that the use of glycerin in the diet can cause localized inflammatory processes, due to its alcoholic feature that degrades the protective mucus barrier and it presents passive absorption and exposes the mucus epithelium to the gastric juice action, thus promoting the mucosa inflammatory process. In the large intestine (cecum and colon) the inflammatory response showed greater intensity as a function of these organs have higher lymphatic tissue (nodular and diffuse)concentration and at this portion the intestine performs the fluids reabsorption directly competing with glycerin which is highly hygroscopic.